Prevalence of hepatitis C in the adult Mexican population: National Survey of Health and Nutrition 2018 - Martha Carnalla; Tonatiuh Barrientos-Gutiérrez; Dèsirée Vidaña-Perez; Martín Romero-Martínez; María Carolina Martínez-Bohorquez; Eduardo González-Pier; Reynerio Fagundo-Sierra; David Kershenobich; Celia Alpuche-Aranda; Eduardo Lazcano-Ponce; Teresa Shamah-Levy (Elsevier, 2022)
Summary: Background: Hepatitis C is a preventable and treatable disease that has been declared a public health problem. In 2012, the prevalence of HCV serum anti-bodies in the Mexican adult population aged 20 to 49 years was 0·30%. Methods: We randomly selected a probabilistic sub-sample of 12,389 adults (20+ years) from adults participating in the National Health and Nutrition Survey (ENSANUT) 2018 who provided a venous blood sample. Anti-HCV antibodies and HCV RNA were determined for this sub-sample. We estimated the national prevalence of anti-HCV antibodies and the proportion with viral RNA detection and evaluated their association with sociodemographic characteristics for all adults and with sexual behaviours in those aged 20 to 49 years using logistic regression. Findings: The national prevalence of anti-HCV antibodies in serum was 0·38% (95%CI 0·24, 0·59) in the population aged 20 years and older; 14·9% of them had viral RNA. In the population aged 20 to 49 years antibody prevalence was 0·23% (95%CI 0·11, 0·48), being higher for males and people living in urban areas. In the population aged 50 years and older, the prevalence was 0·59% (95%CI 0·34, 1·06). Interpretation: The prevalence of antibodies anti-HCV in people aged 20 to 49 years was similar in 2018 than in 2012, suggesting that the prevalence of HCV has remained stable. ENSANUT is a household study and could underestimate the prevalence of HCV. Further efforts must be made to identify cases in non-household populations. Funding: National Institute of Statistics and Geography and National Institute of Public Health of Mexico [CIEE/1807].